Recent Progress on Radical Decarboxylative Alkylation for Csp3–C Bond Formation - Li, Yajun; Ge, Liang; Muhammad, Munira Taj; Bao, Hongli (Synthesis, 2017)
Radical decarboxylation has emerged as an attractive method for the formation of C–C bonds starting from easily accessible carboxylic acids. In this review, we attempt to bring the readers up to date in this rapidly expanding field. Specifically, we will cover recent advances in Csp3–C bond formation via the radical decarboxylation of aliphatic carboxylic acids and their activated forms, such as N-hydroxyphthalimide esters (NHP esters), alkyl diacyl peroxides, alkyl peresters, and aryliodine(III) dicarboxylates. The scope and limitation of these transformations will be discussed, highlighting gaps in knowledge and research and examining the mechanisms underlying radical decarboxylation. We aim to make this review a stepping stone for further development in this field.1 Introduction2 Aliphatic Carboxylic Acids3 N-Hydroxyphthalimide Esters (NHP Esters)4 Alkyl Diacyl Peroxides5 Alkyl Peresters6 Aryliodine(III) Dicarboxylates7 Conclusion
Keywords: radical; carboxylic acids; decarboxylation; redox-active esters; C–C bond formation